Study on Ergonomic Risk Assessment Among Warehouse Workers in An Electronic Manufacturing Industry - Fadlin Afina Suhaimi; Nurrul Hafeezah Sahak (Progress in Engineering Application and Technology, 2024)
The electronic manufacturing is a diverse industry and is susceptible to ergonomic hazards. Warehouse department are likely to expose to ergonomic hazard by their daily job task. Objective of this study are to identify the prevalence of musculoskeletal disorder (MSDs). 19 respondent workers in warehouse department in an electronic manufacturing industry be respondent for this study and cooperate to answer the questionnaire and researcher using the Cornell Musculoskeletal Discomfort Questionnaire (CMDQ). From the analysis conducted and calculation of total discomfort score, body parts which are at risk for injury and discomfort on female workers are wrist, lower leg and foot with percent of 100% each. Male workers shows, the body parts with high risk of injury and discomfort were on the upper back (97.6%), upper arm and thigh with 100% each. Employers are responsible to create awareness about ergonomic besides creating procedures and safe work practices which can lessen the pain and discomfort to the workers. By that, the musculoskeletal disorder (MSDs) risks will be reduced.